Analisis Peran Tata Kelola Kearsipan Dalam Mendukung Efektivitas Dokumentasi Pendidikan Di MA DDI Takkalasi - Nurbia; Hasmiah Herawaty; Rusliman (IAIN Parepare, 2025)
This study aims to describe the archival management system at MA DDI Takkalasi and examine its role in supporting the effectiveness of educational documentation. Archival management has a strategic position in madrasah administration because it is a source of information, authentic evidence of activities, and a basis for decision-making. This study uses a qualitative approach with a case study design that combines literature review, direct observation, and document analysis to gain an in-depth understanding of archival practices. Primary data was obtained through observation of the processes of grouping, storing, organising, and retrieving documents, while secondary data was sourced from official madrasah administration archives. Data analysis was conducted using content analysis techniques, which included reduction, categorisation, and systematic interpretation of findings. The results of the study indicate that archive management at MA DDI Takkalasi has been carried out in a fairly systematic manner through the storage of academic documents, general administration, student archives, and learning activity documents. The archives function effectively in facilitating data retrieval, report preparation, programme planning, and institutional performance evaluation. However, archive management still faces obstacles such as the lack of standard operating procedures, limited storage facilities, and minimal document digitisation. Nevertheless, the madrasah has shown its commitment to improving the quality of its archives by revamping its storage system and strengthening administrative coordination. Overall, records management contributes significantly to supporting the smooth running of educational administration and improving the professionalism of services at MA DDI Takkalasi.